The weevil genera Nyphaeba Pascoe and Pantiala Pascoe and the problems of an unstable nomenclature in orphaned taxa - Riedel, Alexander (Zootaxa, 2017)
The genera Nyphaeba Pascoe and Pantiala Pascoe of Cryptorhynchinae are redescribed and revised. Lectotypes are designated for the names Nyphaeba monommoides Pascoe and Pantiala illusa Pascoe. This facilitates the description of Nyphaeba mimica sp. n. represented by two paralectotypes of Pantiala illusa. Both genera are excluded from the subtribe Tylodina Lacordaire based on their possession of wings and a distinct metanepisternum. The following new combination for a species originally described in Pantiala is proposed: Nyphaeba germari (Faust). A femora-abdominal stridulatory mechanism is observed for Nyphaeba. This case illustrates how nomenclatural problems evident from type material can persist in an understudied taxon for more than a century. Such problems severely affect modern research and databasing.